Intelligibility of British- and American-Accented Sentences for American Younger and Older Listeners With and Without Hearing Loss - Schilaty, Sadie; Ferguson, Sarah Hargus; Morgan, Shae D.; Champougny, Caroline (Journal of the American Academy of Audiology, 2020)
Background Older adults with hearing loss often report difficulty understanding British-accented speech, such as in television or movies, after having understood such speech in the past. A few studies have examined the intelligibility of various United States regional and non-U.S. varieties of English for American listeners, but only for young adults with normal hearing.Purpose This preliminary study sought to determine whether British-accented sentences were less intelligible than American-accented sentences for American younger and older adults with normal hearing and for older adults with hearing loss.Research Design A mixed-effects design, with talker accent and listening condition as within-subjects factors and listener group as a between-subjects factor.Study Sample Three listener groups consisting of 16 young adults with normal hearing, 15 older adults with essentially normal hearing, and 22 older adults with sloping sensorineural hearing loss.Data Collection and Analysis Sentences produced by one General American English speaker and one British English speaker were presented to listeners at 70 dB sound pressure level in quiet and in babble. Signal-to-noise ratios for the latter varied among the listener groups. Responses were typed into a textbox and saved on each trial. Effects of accent, listening condition, and listener group were assessed using linear mixed-effects models.Results American- and British-accented sentences were equally intelligible in quiet, but intelligibility in noise was lower for British-accented sentences than American-accented sentences. These intelligibility differences were similar for all three groups.Conclusion British-accented sentences were less intelligible than those produced by an American talker, but only in noise.
Keywords: aging; hearing loss; speech perception; accent